The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.4315/0362-028x-68.9.1900
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Enterobacter sakazakii in a Dehydrated Powdered Infant Formula

Abstract: A quantity of dehydrated powdered infant formula was prepared to contain Enterobacter sakazakii strain 607 at approximately 106 CFU/ml when rehydrated according to the manufacturer's instructions. The survival of the microorganism in the dry formula was followed for 2 years, during which samples periodically were rehydrated and analyzed for viable E. sakazakii. During the initial 5 months of storage at room temperature, viable counts declined approximately 2.4 log cycles. During the subsequent 19 months, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(46 citation statements)
references
References 15 publications
4
40
1
1
Order By: Relevance
“…were detected in 29% (12/42) of PIF samples, yet none were >2 MPN/100 g (table 1, 2). Edelson-Mammel et al [36] also reported that the concentration of Cronobacter present in US manufactured PIF was frequently below 1 MPN/100 g, corroborating the results of the present study. In Japan, Oonaka et al [37] analyzed a total of 149 samples, of which 61 were of domestic production and 88 imported samples.…”
Section: Resultssupporting
confidence: 82%
“…were detected in 29% (12/42) of PIF samples, yet none were >2 MPN/100 g (table 1, 2). Edelson-Mammel et al [36] also reported that the concentration of Cronobacter present in US manufactured PIF was frequently below 1 MPN/100 g, corroborating the results of the present study. In Japan, Oonaka et al [37] analyzed a total of 149 samples, of which 61 were of domestic production and 88 imported samples.…”
Section: Resultssupporting
confidence: 82%
“…Initial populations decreased by 2 log units immediately following desiccation and by an additional 4 log units during storage for 6 months at an unspecified temperature. Desiccation of cells used in our study and in the study reported by Edelson-Mammel and Buchanan (11) in powdered infant formula caused the death of fewer cells than reported in BHI cultures by Breeuwer et al (4).…”
Section: Vol 71 2005 Performance Of Media For Recovery Of E Sakazamentioning
confidence: 50%
“…Cronobacter strains were isolated from a wide range of foods including milk, cheese, dried foods, meats, water, vegetables, rice, tea, herbs and spices Edelson-Mammel et al 2005;Friedemann 2007), various food production environments and households (Kandhai et al 2004;Gurtler et al 2005). The spectrum of Cronobacter-contaminated foods covers both raw and processed foods and the kind of processing is not restricted to dry products (Friedemann 2007).…”
Section: Introductionmentioning
confidence: 99%